TRP Channels Mediated Pathological Ca2+-Handling and Spontaneous Ectopy - Ezeani, Martin (Frontiers in Cardiovascular Medicine, 2019)
Ion channel biology offers great opportunity in identifying and learning about cardiac pathophysiology mechanisms. The discovery of transient receptor potential (TRP) channels is an add-on to the opportunity. Interacting with numerous signaling pathways, being activated multimodally, and having prescribed signatures underlining acute hemodynamic control and cardiac remodeling, TRP channels regulate cardiac pathophysiology. Impaired Ca2+-handling cause contractile abnormality. Modulation of intracellular Ca2+ concentration ([Ca2+]i) is a major part of Ca2+-handling processes in cardiac pathophysiology. TRP channels including TRPM4 regulate [Ca2+]i, Ca2+-handling and cardiac contractility. The channels modulate flux of divalent cations, such as Ca2+ during Ca2+-handling and cardiac contractility. Seminal works implicate TRPM4 and TRPC families in intracellular Ca2+ homeostasis. Defective Ca2+-homeostasis through TRP channels interaction with Ca2+-dependent regulatory proteins such as sodium calcium exchanger (NCX) results in abnormal Ca2+ handling, contractile dysfunction and in spontaneous ectopy. This review provides insight into TRP channels mediated pathological Ca2+-handling and spontaneous ectopy.